Game Real Time Action RPG Online Berbasis Flash: Alternatif Bermain Game dengan Spesifikasi Perangkat Keras Minimal - Elidjen Elidjen; Paulus Adi Adi Purnomo; Budi Prasetyo (Bina Nusantara University, 2012)
Various games are available for a variety of community as one means of entertainment which is getting more popular these days. However, sometimes several games can not be played on computer due to insufficient hardware specifications support. This situation developed the making of ChainKiller Game, a Flash based real time action RPG online game to provide an alternative as well as interactive and interesting game with a minimum hardware specification. The sequential linear process model is used to develop the overall game. Besides, a literature study was implemented to enrich the insight to develop the interesting mini game. The real-time action RPG online game which is based on Flash can be easyly used with minimum hardware specification.